2011
DOI: 10.4028/www.scientific.net/amr.396-398.1645
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Cashew Apple Wine (CAW)

Abstract: In this study, total polyphenols content (TPC) and ascorbic acid content (AAC) in CAW were quantified. Total antioxidant activity, reducing capacity, and free radical scavenging activity of CAW were assayed. The TPC and AAC were 160 mg GAE /100ml and 132 mg/100 ml,respectivity. CAW exhibited effective antioxidant activities in the employed in vitro experiments, including total antioxidant activity, reducing capacity, and free radical scavenging activity, which indicates that phenolic compounds and ascorbic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Beside CNSL, cashew nut, apple, and testa, cashew apple wine (CAW) had also demonstrated effective antioxidant capacities in the employed in vitro assays. The total polyphenols content and total antioxidant activity were 160 mg GAE/100 mL and 132 mg/100 mL which indicated that phenolic compounds and ascorbic acid may play a pivotal role in the antioxidant function (Zhong & Li, 2012).…”
Section: Functional Properties Of Cashew Bioactive Compoundsmentioning
confidence: 99%
“…Beside CNSL, cashew nut, apple, and testa, cashew apple wine (CAW) had also demonstrated effective antioxidant capacities in the employed in vitro assays. The total polyphenols content and total antioxidant activity were 160 mg GAE/100 mL and 132 mg/100 mL which indicated that phenolic compounds and ascorbic acid may play a pivotal role in the antioxidant function (Zhong & Li, 2012).…”
Section: Functional Properties Of Cashew Bioactive Compoundsmentioning
confidence: 99%
“…Effective methods are carried out in order to purify the TPs from leaching solution. It is known to all that the great majority ways of TPs leaching are put the raw tea leaves in the solvent, such as hot water, alcohol solution, ketone solution or supercritical fluid containing co-solvent etc [4,5] . High temperature and organic solvent could increase the solubility of TPs, however, high temperature could easily inactive TPs to oxidation.…”
Section: Introductionmentioning
confidence: 99%